How has takeover competition changed over time? - Liu, Tingting; Mulherin, J. Harold (Journal of Corporate Finance, 2018)
We study a random sample of completed and withdrawn takeovers during the 1981 to 2014 time period to provide new evidence on the role of takeover impediments such as poison pills, staggered boards and state antitakeover devices. Do such impediments act in the interest of management by promoting entrenchment or do they act in shareholder interest by improving bargaining power during the takeover auction process? We first confirm the growing trend of takeover impediments over time in our sample. We then relate these trends to changes in the takeover auction process over time. Although we corroborate prior findings of a decline in hostile takeovers and publicly reported takeover auctions between the 1980s and later time periods, we find that takeover competition across the entire auction process between deal initiation and completion has not declined. In effect, takeover competition via auctions has gone underground. Moreover, takeover premiums have not declined over time. We interpret the results to be consistent with the shareholder interest/bargaining power hypothesis and inconsistent with the management interest/entrenchment hypothesis. Our analysis highlights the usefulness of research sources for SEC merger documents including microfiche, Lexis Nexis and Thomson One Financial that provide historical information on the takeover auction process prior to the EDGAR filings that started in the mid-1990s.